Digital Leadership in the Framework of Upper Echelon Theory, Impact on SMEs Competitive Advantage: The Role of Innovative Performance - Putra, Rahmat Eka; Chandra, Alhapen Ruslin; Neswardi, Sepri; Chandra, Benny; Nurhayati, Nurhayati (Department of Management, Faculty of Economics and Business, Brawijaya University, 2024)
Innovation plays a crucial role in shaping business competitive advantage. However, there is still little research in the digital era explaining how small and medium enterprises (SMEs) can produce innovative performance amidst rapid technological developments. This study suggests that digital leadership is essential in driving innovative performance to achieve a competitive advantage. Drawing on the upper-echelon theory, this research examines how digital leadership influences competitive advantage through innovative performance. The survey was distributed to owners or managers of SMEs across several industries in Indonesia. A total of 113 SMEs took part in the survey and were included in the data collection. The data was analyzed using structural equation modeling with the AMOS software. The research findings confirm that digital leadership influences SMEs' competitive advantage through innovative performance. Cross-sectional research and a self-report questionnaire are utilized in this investigation. We then engage in a thorough discussion of the research's implications.